Pericardial effusion in patients with COVID-19: case series - Sauer, François (Eur Heart J Case Rep, 2020)
BACKGROUND: SARS-coronavirus-2 [coronavirus disease 2019 (COVID-19)] infection is a public health issue affecting millions of people. It started in Wuhan in China in December 2019 spreading rapidly worldwide. CASE SUMMARY: Three patients aged 51–84 developed a pericarditis related to COVID-19, associated for two of them with a myocarditis. Case 1 was a COVID-19 cardiac tamponade without myocarditis, confirmed by a positive chest computed tomography (CT) scan. Case 2 showed a COVID-19 myopericarditis, confirmed by a positive chest CT scan and a SARS-coronavirus-2 positive swab. Case 3 was a cardiac tamponade due to COVID-19 pericarditis, with a positive polymerase chain reaction on pericardial fluid. They were all treated by colchicine and their condition improved rapidly. DISCUSSION: Presumably rare, we reported three cases of pericardial effusions (PEs) occurring in a single cardiology centre. There is a higher incidence of COVID-19-related cardiac diseases such as pericarditis that can manifest as a minimal PE to a cardiac tamponade, which should result in a higher awareness of cardiologists. A systematic measure of the high-sensitivity troponin kinetic in patients affected by COVID-19 could be interesting in order to screen for potential myocarditis. Any unexplained haemodynamic failure or increased cardiac biomarkers should make the medical team search for myopericarditis by a transthoracic echocardiography.